2020
DOI: 10.1080/15592294.2020.1841871
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal protein malnutrition results in genome-wide disruptions of 5-hydroxymethylcytosine at regions that can be restored to control levels by an enriched environment

Abstract: Maternal malnutrition remains one of the major adversities affecting brain development and longterm mental health outcomes, increasing the risk to develop anxiety and depressive disorders. We have previously shown that malnutrition-induced anxiety-like behaviours can be rescued by a social and sensory stimulation (enriched environment) in male mice. Here, we expand these findings to adult female mice and profiled genome-wide ventral hippocampal 5hmC levels related to malnutrition-induced anxiety-like behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
1
0
1
Order By: Relevance
“…There is evidence that malnutrition during pregnancy is associated with poorer cognitive function in the offspring ( 9 ). Studies in rodents have shown that increasing risk of cognitive disorder is associated with perinatal malnutrition through structural, functional, and molecular changes in brain development ( 10 ). Additionally, malnutrition in an individual during the fetal period and even in the early stages of life is also a risk factor for depression.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that malnutrition during pregnancy is associated with poorer cognitive function in the offspring ( 9 ). Studies in rodents have shown that increasing risk of cognitive disorder is associated with perinatal malnutrition through structural, functional, and molecular changes in brain development ( 10 ). Additionally, malnutrition in an individual during the fetal period and even in the early stages of life is also a risk factor for depression.…”
Section: Introductionmentioning
confidence: 99%
“…Em contrapartida, a exposição ao EA melhora parâmetros moleculares e comportamentais em modelos de estresse, como má nutrição perinatal (ALBERCA et al, 2020;BERARDINO et al, 2019), estresse por imobilização ou contenção (ASHOKAN;HEGDE;MITRA, 2016;BHAGYA et al, 2017;MARIANNO;ABRAHAO;CAMARINI, 2017;MORADI-KOR et al, 2019;NOVAES et al, 2017;SHILPA et al, 2017) e separação ou privação materna (FRANCIS et al, 2002;MENEZES et al, 2020).…”
Section: Introductionunclassified